Evaluasi Kinerja Guru Dalam Peningkatan Mutu Pendidikan Pada Masa Pandemi Covid-19 SD di Negeri Banyuasih II Kabupaten Karawang - Nia Nurarofah; Astuti Darmiyanti (Jurnal Ilmiah Wahana Pendidikan, 2021)
This paper discusses the evaluation of teacher performance in improving the quality of education during the Covid-19 pandemic at Banyuasih II Elementary School, Karawang Regency. The outbreak of the coronavirus or known as Covid-19 in December 2019 in Wuhan caused tremendous anxiety for all Indonesian citizens. Various policies and the implementation of health protocols were carried out to break the chain of the spread of Covid-19, having an impact on teacher performance which affects the quality of education. This study uses a descriptive method with the number of respondents in this study as many as 9 people consisting of all educators at SD Negeri Banyuasih II, Karawang Regency. The results of the study can be seen that indicators that are included in the good category are 78% learning planning, 67% ability to carry out learning, 89% ability to guide and train students, 78% ability to assess learning outcomes, and 89% ability to carry out additional tasks. the lowest performance of educators is the ability to carry out learning. Keyword: Performance, Teachers, Pandemic.